A Transgenerational Effects of Oil Supplemented Diets on Fruit Flies (Drosophila melanogaster) Progenies - Kuswandi, Paramita Cahyaningrum; Pertiwi, Kartika Ratna; Aji, Ibnu Kholdun Sukma (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
AbstractThe causes of obesity are multifactorial, one of which is the parental diet. Fruit fly (Drosophila melanogaster) has homologous genes with humans and is a potential model organism for research on human diseases. This study aims to examine the transgenerational effects of a modified high-fat diet on the number of progenies, sex ratio, and body weight in eight generations of fruit flies. Four types of diets consisted of different fat compositions were used banana, cornmeal, cornmeal + 3% virgin coconut oil (VCO), and cornmeal + 3% palm oil. Data were analyzed using SPSS with ANOVA and DMRT post hoc analysis. Results showed significant differences (P <0.05) in the number of progenies between the diet without oil and with added oil. A higher number of progenies were found in the diet without oil with an average of 85 flies (banana diet) and 85.04 flies (cornmeal diet) compared to the results in the oil diet with 19 flies (cornmeal + 3% VCO) and 76.67 flies (cornmeal + 3% palm oil)The sex ratio and the body weight were not significantly different between each diet, suggesting that there are other factors involved. There were significant differences between the early and late generations for number of progenies and body weight, but not for sex ratio. The VCO was difficult to mix in the media so palm oil has the potential to be used for further investigations to find a better formula for high-fat diet food sources in an obesity study using fruit flies.AbstrakPenyebab terjadinya obesitas bersifat multifaktorial, salah satunya adalah pola makan orang tua. Lalat buah (Drosophila melanogaster) memiliki gen yang homolog dengan manusia dan merupakan organisme model yang potensial untuk penelitian penyakit manusia. Penelitian ini bertujuan untuk menguji pengaruh transgenerasi pola makan tinggi lemak yang dimodifikasi terhadap jumlah keturunan, rasio jenis kelamin, dan berat badan pada delapan generasi lalat buah. Empat jenis pakan dengan komposisi lemak berbeda digunakan yaitu pisang, tepung jagung, tepung jagung + 3% Virgin coconut oil(VCO) dan tepung jagung + 3% minyak sawit. Data dianalisis menggunakan SPSS dengan analisis post hoc ANOVA dan DMRT. Hasil penelitian menunjukkan perbedaan yang signifikan (P <0,05) pada jumlah keturunan, khususnya antara diet tanpa minyak dengan diet dengan minyak. Jumlah progeni yang lebih banyak terdapat pada diet tanpa minyak dengan rata-rata 85 lalat (diet pisang) dan 85,04 lalat (diet tepung jagung) dibandingkan dengan hasil pada diet minyak dengan 19 lalat (tepung jagung + 3% VCO) dan 76,67 lalat (tepung jagung + 3% minyak sawit). Rasio jenis kelamin dan berat badan tidak berbeda secara signifikan antara masing-masing pola makan, hal ini menunjukkan bahwa ada faktor lain yang terlibat. Terdapat perbedaan yang signifikan antara generasi awal dan akhir dalam hal jumlah keturunan dan berat badan, namun tidak untuk rasio jenis kelamin. VCO sulit untuk dicampurkan dalam media sehingga minyak sawit berpotensi digunakan untuk penelitian lebih lanjut untuk menemukan formula sumber makanan diet tinggi lemak yang lebih baik dalam studi obesitas menggunakan lalat buah.